Independence or in-dependence? Non-strict board independence among publicly listed firms - Li Liao, Evan Lance C. (Animo Repository, 2019)
Board independence is thought of as a corporate governance tool that mitigates agency conflicts among firms with either a widely held ownership structure or a highly concentrated ownership structure. As a result, having a high degree of board independence is adopted as the best corporate governance practice in most developed and emerging markets. However, owners of firms with less qualified or non-strict independent directors may not reap the benefits of board independence if such directors are appointed merely for the sake of satisfying quotas or stipulations for best practices. Thus, using data on Philippine publicly listed firms from 2012 to 2015, we construct a measure of non-strict board independence based on the 12 criteria for independence of the 2017 Philippine Corporate Governance Code and examine (1) what type of firm is more likely to appoint non-strict independent directors and (2) the effect of non-strict board independence on firm performance. Using panel data models, we find that firms with a higher ownership concentration are more likely to have non-strict independent directors on the board; however, the presence of these non-strict independent directors do not significantly impact firm performance among firms with high ownership concentration. Our findings support the optimal board independence theory, which posits that non-strict independent directors are appointed primarily to satisfy best corporate governance practices, even if such directors do not have outside expertise or monitoring ability. We conclude that while non-strict independent directors are present among Philippine publicly listed firms, they do not mask any agency problem for firms with large ownership concentration; rather, these directors may have been appointed for the firm to achieve its optimal level of board independence.